Illuminating urban lives - Carvalho, C. (African Studies Review, 2019)
Filip de Boeck and Sammy Baloji.Suturing the City. Living Together in Congo’s Urban Worlds. 2016. United Kingdom: Autograph. 330 pages. Color Photographs. Bibliography. Index. $42.70. Cloth. ISBN: 9781899282197. Sammy Baloji and Filip de Boeck with curator Devrim Bayar. “Urban Now: City Life in Congo.” Exhibited at Galeria Avenida da India, Lisbon, March 24 to June 17, 2018.